Numerical study of turbulent separated flows in axisymmetric diffusers based on a two-fluid model - Kholboev, Bakhodir Murodovich; Malikov, Zafar M.; Madaliev, Murodil Erkinjon ugli; Shoev, Mardon; Masharipov, Sirojiddin (Zielona Góra: Uniwersytet Zielonogórski)
The study presented the results of numerical simulations using well-known turbulence models: the two-parameter SST model and the one-parameter SA model, built into the Comsol Multiphysics software package. It was found that the two-fluid turbulence model in the Comsol Multiphysics software package provides more accurate results compared to the considered models. In addition, a higher degree of convergence and stability of this model was noted than the standard turbulence models that are built into Comsol Multiphysics.
Keywords: Navier-Stokes equations; axisymmetric diffuser; separated flow; turbulent flow; two-fluid model